Accumulation and transformation of azaspiracids in scallops (Chlamys farreri) and mussels (Mytilus galloprovincialis) fed with Azadinium poporum, and response of antioxidant enzymes. (1st March 2018) - Ji, Ying; Qiu, Jiangbing; Xie, Tian; McCarron, Pearse; Li, Aifeng
Abstract: Azaspiracid (AZA) producing microalgae have been reported internationally and could potentially impact a variety of seafood. Scallops ( Chlamys farreri ) and mussels ( Mytilus galloprovincialis ) from China were fed with the AZA2 producer, Azadinium poporum, to study uptake, metabolism and oxidative stress in the shellfish. LC-MS/MS showed significant accumulation and differential metabolism of AZA2 in the scallops and mussels. In mussels AZA2 was metabolized to AZA19, with subsequent decarboxylation to AZA6. In scallops no AZA19 or AZA6 was observed, however, a novel AZA metabolite was formed that is isobaric with AZA19 ( [M+H] +, m/z 886), but elutes at a different retention time. In addition it was noted that the scallop metabolite was stable during heating, while AZA19 has been shown to decarboxylate. Concentrations of reactive oxygen species (ROS) and activities of antioxidant enzymes were monitored. ROS levels increased slightly in the meat of scallops and mussels due to starvation in the acclimation and depuration periods, but reduced in the feeding periods with non-toxic Isochrysis galbana or toxic A. poporum . No obvious variations were found in activities for a range of antioxidant enzymes. These results provide new insights on the potential for accumulation and metabolism of AZAs in bivalve species relevant to this area of China, which is of importance considering the recent finding of AZA producing microalgae in the region. Graphical abstract: Highlights: Chlamys farreri and Mytilus galloprovincialis were fed with AZA2 producer, Azadinium poporum. Different conversion of AZA2 was found in the experimental scallops and mussels using LC-MS/MS. In mussels AZA2 was metabolized to AZA19, with subsequent decarboxylation to AZA6. No AZA19, but a novel metabolite was formed with the same mass as AZA19 ([M+H] + = 886) in scallops. Obvious effects of toxins on the antioxidant enzymes were not found in the both shellfishes.